On shear layer atomization within closed channels: Numerical simulations of a cough-replicating experiment - Pairetti, César; Villiers, Raphaël; Zaleski, Stéphane (Computers & fluids, 2021)
Aerosol generation during coughing and sneezing has gained major relevance due to the current COVID pandemic. The atomization involved in this process takes place in the complex context of the respiratory system and develops very rapidly. In order to get further insights on the early spray generation, we introduce a simplified model of physiological coughing or sneezing, in the form of a thin liquid layer subject to a rapid (30 m/s) air stream. The setup is simulated using the Volume-Of-Fluid method with octree mesh adaptation, the latter allowing grid sizes small enough to capture the Kolmogorov length scale. The results confirm the trend to an intermediate distribution between a Log-Normal and a Pareto distribution P(d)∝d−3.3 for the distribution of droplet sizes in agreement with a previous re-analysis of experimental results by one of the authors. The mechanism of atomization does not differ qualitatively from the multiphase mixing layer experiments and simulations. No mechanism for a bimodal distribution, also sometimes observed, is evidenced in these simulations.